2007
DOI: 10.1152/ajpgi.00415.2006
|View full text |Cite
|
Sign up to set email alerts
|

TwoN-linked glycans are required to maintain the transport activity of the bile salt export pump (ABCB11) in MDCK II cells

Abstract: The aim of this study was to determine the role of N-linked glycosylation in protein stability, intracellular trafficking, and bile acid transport activity of the bile salt export pump [Bsep (ATP-binding cassette B11)]. Rat Bsep was fused with yellow fluorescent protein, and the following mutants, in which Asn residues of putative glycosylation sites (Asn109, Asn116, Asn122, and Asn125) were sequentially replaced with Gln, were constructed by site-directed mutagenesis: single N109Q, double N109Q + N116Q, tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…TC transport activity was evaluated, as described previously (Mochizuki et al, 2007). In brief, MDCK II cells were replated on Transwell membrane inserts (no.…”
Section: Methodsmentioning
confidence: 99%
“…TC transport activity was evaluated, as described previously (Mochizuki et al, 2007). In brief, MDCK II cells were replated on Transwell membrane inserts (no.…”
Section: Methodsmentioning
confidence: 99%
“…BSEP is a glycoprotein with four putative N-linked glycosylation sites and with a molecular weight of 140 to 170 kDa [34, 94,100,217,240]. Rat Bsep is glycosylated at all four putative glycosylation sites [225]. In addition to glycosylation, phosphorylation of Bsep [114,238] and ubiquitination occur as additional posttranslational modifications.…”
Section: Molecular Propertiesmentioning
confidence: 99%
“…Mutagenic removal of one or two of the four N-glycosylation sites from the apical bile salt export pump (ABCB11) did not significantly affect its stability, trafficking, or function (56). However, removal of three or all four N-glycosylation sites dramatically increased the rate of proteasome-dependent degradation and resulted in significant intracellular retention of the protein.…”
Section: Role Of N-glycans In Protein Folding Stability and Qualitymentioning
confidence: 99%
“…However, removal of three or all four N-glycosylation sites dramatically increased the rate of proteasome-dependent degradation and resulted in significant intracellular retention of the protein. Comparison of mutants of ABCB11 with various combinations of mutated glycosylation sites showed that presence of at least two N-glycans is required for normal folding and trafficking of the protein (56).…”
Section: Role Of N-glycans In Protein Folding Stability and Qualitymentioning
confidence: 99%
See 1 more Smart Citation